Training in Water Emergency First Aid using a Simulation Method to Improve the Knowledge of Pokdarwis Sumber Complang, Pranggang Village - Alfian Fawzi; Hengky Irawan; Dimas Yuana Putra; Dias Andrika; Intan Meliasari; Brigita Putri Febrianti; Putri Devita Sari; Aprilia Nuril Hidayanti; Else Auvi Dalilah; Berlyta Eka Divany; Nova Rellyta; Nurohmah (Universitas STRADA Indonesia, 2025)
Knowledge of first aid for drowning victims among communities near water attractions is essential to improve the success of assistance, especially for tourism awareness groups (Pokdarwis). Proper first aid knowledge is necessary to the reduce mortality and morbidity of accident victims, as the level of knowledge will affect the handling techniques for accident victims before they are taken to the hospital. However, currently, very little education is provided to the community as first responders at the scene. Therefore, the PPK ORMAWA BEM STRADA INDONESIA team conducted training on first aid for drowning victims for Pokdarwis and the community around Sumber Complang, Pranggang Village, to increase awareness and success when assistting. This activity aims to determine the relationship between increased knowledge of Pranggang Village Pokdarwis and helping drowning victims using the simulation method. The results obtained show a p-value of 0.004. Since 0.004 is less than < 0.05, it can be concluded that there is a difference in respondents' abilities before and after training. An effective simulation method can easily teach someone to understand new knowledge. These results indicate that the simulation method is very effective in training lay people to perform first aid for drowning victims.